2021
DOI: 10.1186/s12955-021-01692-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Chinese version of Five Facet Mindfulness Questionnaire—short form in cancer patients: a Bayesian structural equation modeling approach

Abstract: Background Mindfulness has emerged as an important correlate of well-being in various clinical populations. The present study evaluated the psychometric properties of the 20-item short form of the Five Facet Mindfulness Questionnaire (FFMQ-SF) in the Chinese context. Methods The study sample was 127 Chinese colorectal cancer patients who completed the FFMQ-SF and validated physical and mental health measures. Factorial validity of the FFMQ-SF was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…However, whilst this method has been validated in one study [ 29 ], it cannot yet be considered robust. This is particularly important considering that acting with awareness can predict lower levels of perceived stress [ 43 ], something the present study suggests may also be the case in early year medical students but does not prove. Future studies employing such tools may provide deeper understanding of how respondents are stressed.…”
Section: Discussionmentioning
confidence: 60%
“…However, whilst this method has been validated in one study [ 29 ], it cannot yet be considered robust. This is particularly important considering that acting with awareness can predict lower levels of perceived stress [ 43 ], something the present study suggests may also be the case in early year medical students but does not prove. Future studies employing such tools may provide deeper understanding of how respondents are stressed.…”
Section: Discussionmentioning
confidence: 60%
“…The present study sample comprised 184 stroke survivors in Hong Kong, who were recruited under convenience sampling via centres of community rehabilitation network and a local hospital from 2019 to 2021. The present study had a larger sample size than those reported in previous psychometric studies (N = 114-146) [27][28][29] and a subject to item ratio of 184:12 = 15.3. The inclusion criteria were experience of a stroke event, aged between 18 and 64, and ability to understand Chinese.…”
Section: Methodsmentioning
confidence: 88%
“…In addition, a recent study continued to confirm the psychometric properties of the Chinese version in patients with cancer using a Bayesian structural equation modeling approach. 74 We used the Chinese version in this study, which had an overall Cronbach's alpha coefficient of 0.644, 0.704, 0.731, and 0.749 ​at T0, T1, T2, and T3, respectively, to measure mindfulness.…”
Section: Methodsmentioning
confidence: 99%